2022
DOI: 10.1080/21655979.2022.2068783
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4739 inhibits the malignant behavior of esophageal squamous cell carcinoma cells via the homeobox C10/vascular endothelial growth factor A/phosphatidylinositol 3-kinase/AKT pathway

Abstract: Esophageal cancer is a lethal disease, and emerging evidence has shown that microRNAs are involved in its development, progression, and clinical outcome. MicroRNAs are potential biomarkers for esophageal squamous cell carcinoma (ESCC), and may be useful in advanced RNA therapy for ESCC. This study was conducted to evaluate the molecular mechanism of miR-4739 in ESCC. Reverse transcription-quantitative polymerase chain reaction and western blotting were performed to measure RNA and protein levels. Transwell ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Additionally, in gastric cancer, miR-4739 has been found to play a negative role in TYMSOS, thereby suppressing cell proliferation, migration, and invasion [ 27 ]. Furthermore, in the case of ESCC, the overexpression of miR-4739 has shown remarkable potential in inhibiting cell proliferation, migration, and invasion, while concurrently promoting apoptosis [ 17 ]. Collectively, these findings provide further evidence of the tumor-suppressive role of miR-4739 across multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in gastric cancer, miR-4739 has been found to play a negative role in TYMSOS, thereby suppressing cell proliferation, migration, and invasion [ 27 ]. Furthermore, in the case of ESCC, the overexpression of miR-4739 has shown remarkable potential in inhibiting cell proliferation, migration, and invasion, while concurrently promoting apoptosis [ 17 ]. Collectively, these findings provide further evidence of the tumor-suppressive role of miR-4739 across multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that miR-4739 is downregulated in gastric cancer [ 13 ], prostate cancer [ 14 ], and lung adenocarcinoma [ 15 ], while it is upregulated in hepatocellular carcinoma [ 16 ]. In terms of functionality, increased expression of miR-4739 has been observed to inhibit the growth of esophageal squamous cell carcinoma (ESCC) cells by suppressing the expression of homeobox C10 [ 17 ]. Nevertheless, there is a lack of information regarding the function and molecular mechanism of miR-4739 in relation to chemoresistance in CC cells.…”
Section: Introductionmentioning
confidence: 99%